Chile integrates local technical agroclimatic committees into National climate adaptation plan for agriculture - Castellanos, Andrea Estefania; Martinez Baron, Deissy (2025)
The Ministry of Agriculture of Chile has integrated Local Technical Agroclimatic Committees (LTACs, MTAs in Spanish) into its updated Climate-Change Adaptation Plan for the Silvoagricultural Sector (PACC SAP), with technical support from the Alliance of Bioversity International and CIAT. The government has committed to establishing or operationalizing at least three MTAs (2024–2028), and four MTAs in the Aysén Region as part of a Pilot Climate Adaptation Plan, strengthening climate-risk management for farmers in the Aysén Region.